An uncommon entero-genital malformation in the adult: Intestinal duplication - Rodríguez De Armas, Ramón; Graglia, Graciela; Remedio, Gloria (Cirugía del Uruguay, 1979)
A 42 - year - old woman, with no pathofogic antecedents worth mentioning, developed acute abdominal symptoms and was operated. Findings were unexpected, in total discrepancy with established diagnosis. Closed and incomplete intestinal duplication of colon; anomalous peritonized wall on right side, separating annexe from the rest of genital apparatus. Surgical solution proved good and there was no malignancy; prognosis was consequently favourable. We have reported this condition by reason of its being extremely rare in adults.